Combination of Leunca Herb Ethanolic Extract and Doxorubicin Suppresses HeLa Cellsâ Growth - Sarmoko, .; Putri, Dyaningtyas D. P.; Puspitasari, Endah; Anindyajati, .; Meiyanto, Edy (Indonesian Research Gateway, 2011)
Leunca (Solanum nigrum L.)ethanolic extractshowedcytotoxic activity on several cancerÂ cell lines (HepG2, HT-29) and showed anti-proliferative activityon MCF-7 cells. Its applicationÂ as a combinationagent in chemotherapy will increase Â the effectivity and reduce Â the toxicity ofÂ chemotherapy. We predict that application of combinatorial chemotherapy in cancer treatmentÂ will Â be Â more Â effective Â and Â less Â toxic Â compared Â to Â single Â treatment. Â Our Â research Â aims Â toÂ investigate Â the Â cytotoxic Â activitiy Â of Â leunca Â herbs Â ethanolic Â extract Â alone Â and Â in Â combinationÂ with Â doxorubicin Â on Â HeLa Â cell Â line. Â MTT Â assay Â was Â conducted Â to Â measure Â the Â growthÂ inhibitory Â effect Â of Â leunca Â herbs Â ethanolic Â extract Â and Â combinatorial Â treatments. Â Leunca Â herbÂ ethanolic extract (5, 50, 250 Î¼g/ml) increased the cytotoxic effect of Â doxorubicin compared toÂ doxorubicin alone. The strongest cytotoxic activity resulted from the combination of 250 Î¼g/mlÂ leunca Â herbs Â ethanolic Â extract Â and Â 250 Â nM Â doxorubicin. Â Based Â on Â our Â results, Â leunca Â herbsÂ ethanolic extract is a potential chemopreventive agent, while its molecular mechanism needs toÂ be explored.Keyword : Leunca herbs ethanolic extract, doxorubicin, HeLa, MTT assay